Shoot to kill - Miers, Richard; Festing, Francis, Sir, 1902-1976 (London, Faber and Faber, 1959)
Account of the war against the communist terrorists in Malaya, by the commander of a Welsh battalion which participated in 1955.
Keywords: Jungle warfare; Malaya -- History; Malaisie occidentale -- Histoire; History